A REVIEW ON APPLICATIONS OF PROBIOTICS IN HUMAN HEALTH AND DISEASE - Pakdaman, Yasaman (Journal of Biomedical and Pharmaceutical Research, 2019)
The emergence of resistance and tolerance to the existing drugs has created a decreased efficacy of these drugs in use. Along with the advancement in other fields of medicine, the problem of resistance has been tried to be overcome by increasing the drug delivery to the target site by the use of polymers or through nanotechnology, synthesis of new drugs, either by the use of proteomics or synthesis from lactic acid bacteria, or marine microorganisms. Recent research has revealed a potential therapeutic role for the manipulation of the microbiota in the maintenance of human health and treatment of various mucosal disorders. Probiotic microorganisms can shape the immune system both at the local and systemic level which will allow future probiotics as treatments for many diseases. The benefits include either a shortened duration of infections or decreased susceptibility to pathogens.                   Probiotic bacteria have multiple and various influences onthe host. Different organisms can influence the intestinal luminal environment, epithelial and mucosal barrier function, and the mucosal immune system. The numerous cell types affected by probiotics involve epithelial cells, dendritic cells, monocytes/macrophages, B cells, T cells. Probiotics do not always colonize the intestinal tract to exert their effects. Some probiotics like Bifidobacterium longum become part of the human intestinal microflora, whereas others like Lactobacillus casei indirectly exert their effects in a transient manner as they pass through by remodeling or influencing the existing microbial community.          Probiotics seem to have promising role in shortening duration of infections or decreasing susceptibility to the pathogens. Incorporation of probiotics in nutrition as a means of derivation of health benefits. The best documented effects include bowel disorders such as lactose intolerance, antibiotic-associated diarrhea and infectious diarrhea, emerging evidence accumulates concerning their potential role in various other conditions. In the same time as relevant consumer awareness grows, such products are becoming increasingly popular and tend to represent one of the largest functional food markets.Key words: probiotics, Antibiotic associated diarrhea, microorganisms, Antibiotic resistance, Lactic acid bacteria.